108 Systemic review of allergies and treatment to components of cardiac implantable electronic devices. (4th June 2021) - Dissanayake, Tharindra; Shah, Parin; Margulescu, Andrei; Thomas, Dewi; Barry, James
Abstract : Background: Components of Cardiac Implantable Electronic Devices (CIEDs) consist of polymers and metallic alloys. Although they are rare, there are documented cases of allergic reactions to components of CIEDs. These are commonly misdiagnosed as device pocket infections leading to wasted resources and potentially serious consequences for the patient. Methods: We conducted a systematic literature review to identify reported cases of allergic reactions to components of CIEDs and their treatment/management. The words 'pacemaker', 'cardiac implantable electronic device', 'cardiac rhythm device', 'implantable cardiac defibrillator' or ' cardiac resynchronization therapy' in combination with 'replacement' or 'treatment' were used as search criteria. Results: We identified a total of 32 case reports of Allergic reactions to components of CIEDs. Of these 25 were PPMs (Permanent Pace Makers) and 7 were ICDs (Implantable Cardioverter Defibrillator) (1 CRTD - Cardiac Resynchronization Therapy Device). 18 reported hypersensitivity reactions were to alloys or metals and 13, due to polymers. In 1 case, patch testing showed positivity to multiple allergens but a single, causative material was not identified. The onset of symptoms as a result of these reactions showed wide variation, ranging from 1 day to 10 years post CIED implant. The most common metal allergen was Titanium and the most common polymer was Epoxy Resin. Patient's history, clinical examination and patch testing were used to diagnose allergic reactions to CIED components. Management of the allergic reactions varied depending on the severity. Topical steroids were used for limited cutaneous reactions, while in more deep seated reactions, a complete system extraction with re-implantation of a Gold coated CIED was performed. Conclusion: Allergic reactions to CIEDs are rare but important complications. It is important to identify this pathology early in order to manage patients optimally to minimize harm. Conflict of Interest: None